Catalyzing Change: Factors Influencing Employees’ Change Readiness in Banking industry - Maulia, Indah Rizki; Rony, Zahara Tussoleha; Ali, Hapzi (International Journal of Innovation Research in Education, Technology and Management, 2024)
The purpose of this study is to find out factors that influencing employee’s change readiness especially in Banking industry. The method used for this study is systematic literature review (SLR) using articles obtained from international journals indexed in Scopus Q1, Q2, Q3, and Q4 .This study finds that factors influencing employees’ change readiness in Banking industry are: affective commitment, employees' positive perceptions of training programs, perceived competence, perceived autonomy, perceived relatedness, codification strategy, and personalization strategy, Islamic work ethics, organizational commitment, Human Resource Competency 4.0, soft skill training, individual characteristics, transformational leadership, employee commitment to change and transformational entrepreneurship.